Differentially Expressed Genes in Hepatopancreas of Acute Hepatopancreatic Necrosis Disease Tolerant and Susceptible Shrimp (Penaeus vannamei) - Mai, Hung N; Caro, Luis Fernando Aranguren; Cruz-Flores, Roberto; White, Brenda Noble; Dhar, Arun K. (Frontiers in Immunology, 2021)
Revised Abstract Acute hepatopancreatic necrosis disease (AHPND) is a lethal disease in marine shrimp that has caused large-scale mortalities in shrimp aquaculture in Asia and the Americas. The etiologic agent is a pathogenic Vibrio sp. carrying binary toxin genes, pirA and pirB in plasmid DNA. Developing AHPND tolerant shrimp lines is one of the prophylactic approaches to combat this disease. A selected genetic line of Penaeus vannamei was found to be tolerant to AHPND during screening for disease resistance. The mRNA expression of twelve immune and metabolic genes known to be involved in bacterial pathogenesis were measured by quantitative RT-PCR in two populations of shrimp, namely P1 that showed susceptibility to AHPND, and P2 that showed tolerance to AHPND. Among these genes, the mRNA expression of chymotrypsin A (ChyA) and serine protease (SP), genes that are involved in metabolism, and crustin-P (CRSTP) and prophenol oxidase activation system 2 (PPAE2), genes involved in bacterial pathogenesis in shrimp, showed differential expression between the two populations. The differential expression of these genes shed light on the mechanism of tolerance against AHPND and these genes can potentially serve as candidate markers for tolerance/susceptibility to AHPND in P. vannamei. This is the first report of a comparison of the mRNA expression profiles of AHPND tolerant and susceptible lines of P. vannamei.